Boosting photocatalytic performance for selective oxidation of biomass-derived pentoses and hexoses to lactic acid using hierarchically porous Cu/Cu2O/CuO@CA. Issue 46 (18th October 2021) - Jin, Dongnv; Jiao, Gaojie; Ren, Wenfeng; Zhou, Jinghui; Ma, Jiliang; Sun, Runcang
Abstract : Boosting photocatalytic performance for selective oxidation of biomass-derived pentoses and hexoses to lactic acid using hierarchically porous Cu/Cu2 O/CuO@CA. Abstract : Photocatalytic-reforming of biomass-derived feedstocks to high-value added chemicals is highly desired, yet limited success has been achieved. To this aim, the development of an efficient, cost-effective, and environmentally friendly photocatalyst is essential. Here, a flower-shaped Cu/Cu2 O/CuO composite homogeneously inlayed in the carbon nanosheets of a flexible carbon aerogel (Cu/Cu2 O/CuO@CA) was developed via a freeze-drying-calcination strategy, in which the CuO nanobelt precursor was partly converted to Cu and Cu2 O. The obtained photocatalyst exhibited excellent and rapid activity in the photocatalytic-reforming of biomass-derived pentoses and hexoses to lactic acid. The photocatalyst also showed excellent stability and reusability, and its practicability was demonstrated in a scale-up experiment. This work paves that phase transition of copper oxide species on carbon nanosheets of aerogels can effectively improve and accelerate the activity of photocatalytic biomass refining.